2008
DOI: 10.1021/nn700424u
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Relative Barrier Heights in Molecular Electronic Junctions with Transition Voltage Spectroscopy

Abstract: Though molecular devices exhibiting potentially useful electrical behavior have been demonstrated, a deep understanding of the factors that influence charge transport in molecular electronic junctions has yet to be fully realized. Recent work has shown that a mechanistic transition occurs from direct tunneling to field emission in molecular electronic devices. The magnitude of the voltage required to enact this transition is molecule-specific, and thus measurement of the transition voltage constitutes a form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

59
392
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(454 citation statements)
references
References 43 publications
59
392
3
Order By: Relevance
“…[34,161,162] Experimentally, it is fairly simple to identify this transition bias (V T ) and indeed, in the study cited, [34,161,162] V T correlated well with the expected barrier height, the difference of the molecular level (highest occupied molecular orbital, HOMO) and the electrode Fermi level as deduced independently by UPS (see, however, Section 5.2). [52,161,162] This approach assumes a roughly linear J-V relation for tunneling transport [161] (i.e., positive ln(J/V 2 ) vs. 1/V slope), and in that case V T indeed indicates a change in transport mechanism to field-emission. However, as the barrier width/height ratio (which we called ''shape factor'' [149,159] ) increases, the tunneling J-V becomes more non-linear.…”
Section: Extracting Insulator Parameters From Current-density-voltagementioning
confidence: 52%
See 1 more Smart Citation
“…[34,161,162] Experimentally, it is fairly simple to identify this transition bias (V T ) and indeed, in the study cited, [34,161,162] V T correlated well with the expected barrier height, the difference of the molecular level (highest occupied molecular orbital, HOMO) and the electrode Fermi level as deduced independently by UPS (see, however, Section 5.2). [52,161,162] This approach assumes a roughly linear J-V relation for tunneling transport [161] (i.e., positive ln(J/V 2 ) vs. 1/V slope), and in that case V T indeed indicates a change in transport mechanism to field-emission. However, as the barrier width/height ratio (which we called ''shape factor'' [149,159] ) increases, the tunneling J-V becomes more non-linear.…”
Section: Extracting Insulator Parameters From Current-density-voltagementioning
confidence: 52%
“…[149,159,161,162] One approach postulates that if the applied bias is larger than the barrier height, the transport mechanism changes from direct tunneling to field-emission. [34,161,162] Experimentally, it is fairly simple to identify this transition bias (V T ) and indeed, in the study cited, [34,161,162] V T correlated well with the expected barrier height, the difference of the molecular level (highest occupied molecular orbital, HOMO) and the electrode Fermi level as deduced independently by UPS (see, however, Section 5.2). [52,161,162] This approach assumes a roughly linear J-V relation for tunneling transport [161] (i.e., positive ln(J/V 2 ) vs. 1/V slope), and in that case V T indeed indicates a change in transport mechanism to field-emission.…”
Section: Extracting Insulator Parameters From Current-density-voltagementioning
confidence: 99%
“…Their studies revealed that the dominant mechanism of charge transport across these junctions was tunneling for molecular wires shorter than ~ 4 nm, but the mechanism changed to hopping for molecular wires exceeding ~ 4 nm in length. Beebe et al 38,39 showed that A generally accepted mechanism to explain the difference in values of β in "insulating" media is super-exchange tunneling. 44 Interactions of the electrons with the orbitals of the organic molecule increase the probability of tunneling, and make "through-bond" tunneling more efficient than "through-space" tunneling.…”
Section: Mechanisms Of Charge Transport Across Sams Three Different mentioning
confidence: 99%
“…Beebe et al 38,39 described a method to estimate this barrier height. Near zero bias, the barrier shape is rectangular and eq.…”
Section: Mechanisms Of Charge Transport Across Sams Three Different mentioning
confidence: 99%
See 1 more Smart Citation